An Ontological Approach to Analyze the Data Required by a System Quality Scheme - Blas, María Julia (2015)
According to IEEE, software quality is the degree to which software possesses a desired combination of attributes. Quality attributes have been of interest to the software community since 1970 and in the past few years this interest has increase. However, still is not clear how product quality should apply in the development process. The need to know what quality characteristics influence a specific entity and which is the information required to cover its measurement is the objective of this work. This paper presents an ontology to document a quality scheme with a specification based on ISO/IEC 25010. This contribution includes rules and queries that help to determine the data required to carry out the measurement process.